The Students’ Voices on the Use of Blended Learning Model in Teaching English - Jihan Nur Faatihah DM; Muhammad Basri Jafar; Maemuna Muhayyang (EduLine: Journal of Education and Learning Innovation, 2024)
This qualitative method with a case study aims to describe the students’ perception of blended learning model use in teaching and learning English as a foreign language. The research subjects were the tenth-grade students of SMAN 11 Makassar consisting of 38 students taken purposely as the sample of this research. It used semi-structured interviews as the instrument to collect the data needed using narrative analysis with the framework of qualitative analysis developed by Miles and Huberman (1994) into four elements, namely data collection, data reduction, data display, and conclusion. It was found that the students positively and negatively perceived the use of blended learning models in learning English. The positive perception was indicated by their good responses, actions, and attitudes, that is a feeling good about learning, a comfortable classroom atmosphere, and a feeling of motivation to learn. Conversely, the students are negatively perceived due to their bad responses, actions, and attitudes, namely a feeling confused about learning, uncomfortable classroom interaction and atmosphere, and feeling demotivated in learning. These findings take into consideration that the use of blended learning may lead the students to gain either a good or bad learning mood in teaching English classroom interaction.